Disease burden of aortic aneurysm from 1990 to 2021 with a forecast to 2045: insights from the global burden of disease 2021 - Cuihong Tian; Xuan Zhang; Haoxian Tang; Nan Luo; Jingtao Huang; Hanyuan Lin; Qinglong Yang; Yequn Chen; Xuerui Tan (BMC Public Health)
Abstract Introduction Aortic aneurysm is one of the causes of cardiovascular disease-related death, posing a significant challenge to global healthcare. Understanding the burden of aortic aneurysm is crucial for formulating effective public health intervention policies and allocating resources. The study aims to assess the global, regional, and national burden, trend, and inequalities of aortic aneurysm. Methods Aortic aneurysm-associated mortality, disability-adjusted life-years (DALYs), age-standardized mortality rate (ASMR), age-standardized disability-adjusted life-years (ASDR), and their average annual percentage change (AAPC) were estimated based on a population-based study, the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. The global, regional, and national burden of aortic aneurysm was analyzed across 204 countries and territories from 1990 to 2021, stratified by sex, sociodemographic index (SDI), and further predicted to 2045. Results The ASMR decreased from 2.54 per 100,000 population in 1990 to 1.86 per 100,000 population in 2021, with an AAPC of -0.99%. The ASDR declined from 48.79 per 100,000 population in 1990 to 36.54 per 100,000 population in 2021, with an AAPC of -0.90%. The most significant decline in ASDR was observed among males (-1.14% vs. -0.68% per year). ASMR increased considerably, especially in countries with a low-middle SDI (1.29% per year), while it dropped particularly in countries with a high SDI (-1.65% per year). Notably, though the number of mortality and DALYs was predicted to continue rising, the ASMR and ASDR for aortic aneurysm were projected to decrease annually from, with predicted values of 1.92 per 100,000 population and 40.38 per 100,000 population in 2045, respectively. Conclusions The global relative burden of individuals with aortic aneurysm decreased since 1990, along with a prominent decrease in related ASMR and ASDR. Aortic aneurysm-related mortality and DALYs were higher in males and those living in regions with a high SDI.